Birth Control in Lima, Peru - Hall, M. Francoise (1966)
It was carried out a case study of pregnancies and contraceptive methods used by a random sample of 500 women in Lima, Peru . During the five years preceding the interview, the proportion of pregnancies ending in abortions was 19 , 20 and 15 % in the socio- economic middle and lower respectively upper levels . Although the percentage of induced abortions was admitted as low , the rate of abortions was considered relatively high , and it was thought that probably included many whose provocation induced abortions but was not admitted . The suspicions were substantiated when abortions rates were tabulated by age of women and pregnancy order . It can be concluded that induced abortions are a method of controlling fertility in Lima, especially in the high and middle socio- economic levels, and women over 30 who already have 3 or 4 children , are which mainly resort to induced abortions . We found that contraceptive methods were widely practiced , especially the socio- economic upper and middle groups. The proportion of women at risk of pregnancy who were using a contraceptive method at the time the interview was conducted was 68 , 55 and 38% in the high , middle and lower socioeconomic groups respectively . The condom was one of the two most popular contraceptive methods in the three social classes . In the upper and middle socio- economic levels, the rhythm method was also popular, while douching and withdrawal were also popular in the lower level. In all groups , the majority of women were in favor of limiting the family.